Seed-Derived Ethylene Facilitates Colonization but Not Aflatoxin Production by Aspergillus flavus in Maize - Wang, Shi; Park, Yong-Soon; Yang, Yang; Borrego, Eli J.; Isakeit, Tom; Gao, Xiquan; Kolomiets, Michael V. (Frontiers in Plant Science, 2017)
Ethylene (ET) emitted by plant tissues has been broadly reported to play important roles in plant development, response to environmental stresses and defense against certain pathogens. Recent evidence obtained from using in vitro fungal cultures exposed to ET suggested that exogenous ET may regulate the production of aflatoxin by Aspergilli. However, the function of endogenous, seed-derived ET has not been explored. In this study, we found that the maize lipoxygenase lox3 mutant, previously reported to be susceptible to Aspergillus spp., emitted greater levels of ET upon A. flavus infection, suggesting the potential involvement of endogenous ET in the susceptibility of maize to A. flavus. Supporting this idea, both colonization and conidiation of A. flavus were reduced in wild-type (WT) kernels treated with AgNO3, an ET synthesis inhibitor. There was no ET emission from nonviable kernels colonized by A. flavus, suggesting that living seed but not the fungus itself was the primary source of ET released upon infection with A. flavus. The kernels of acs2 and acs6, two ET biosynthetic mutants carrying Mutator transposons in the ACC synthase genes, ACS2 and ACS6, respectively, displayed enhanced seed colonization and conidiation, but not the levels of aflatoxin, upon infection with A. flavus. Surprisingly, both acs2 and acs6 mutant kernels emitted greater levels of ET in response to infection by A. flavus as compared with WT seed. The increased ET in single mutants was found to be due to overexpression of functional ACS genes in response to A. flavus infection. Collectively, these findings suggested that ET emitted by infected seed facilitates colonization by A. flavus but not aflatoxin production.